OPTIMIZATION OF SMALL BUSINESS DEVELOPMENT STRATEGY WITH THE BLUE OCEAN METHOD (Case Study at Katamata Coffee & Roastery in Gunungkidul) - Ika Yuni Astuti; Dwi Aulia Puspitaningrum (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Katamata Coffee & Roastery is one of the coffee shops in Gunungkidul and started in 2016. The increasing trend of visiting coffee shops has certainly impacted competition. This study aims to (1) make a sales forecast for the next 12 months, (2) identify internal and external factors for Katamata Coffee & Roastery, and (3) make appropriate strategic decisions in Katamata Coffee & Roastery business development. This research uses quantitative with descriptive analysis. The analysis technique uses quadratic trend, IFE, EFE, IE, and Blue Ocean Strategy. The results show that (1) sales forecasting for the next 12 months shows that data has an increasing trend, (2) internal factor in Katamata Coffee & Roastery, which received the highest score for strength that it has good product quality and various types of coffee and the main weakness is the lack of promotional activities. The external factor that had the highest score for opportunity is participating in UMKM activities in Gunungkidul, and the main threat is the emergence of new competitors. Based on the IE matrix, Katamata is in cell V, which means the company must hold and maintain its position, and (3) decision-making used by the blue ocean method had the results in reduced purchasing raw materials of coffee that used to be less popular, increasing quality control, increasing size of the parking area, increasing online and offline promotion activities, increasing non-cash payment facilities, creating innovative custom coffee products, and creating a unique coffee shop concept.